Understanding HRIS adoption: a psychosocial perspective on managerial engagement and system effectiveness - Sofi, Fadi; Al-Fattal, Anas; Fan, Ip-Shing (MDPI, 2025)
Human Resource Information Systems (HRISs) have become integral to contemporary organizational life, yet their successful adoption remains uneven and poorly understood. Existing models often focus on cognitive or technical determinants, overlooking how emotional and social factors shape user behavior in real-world settings. This study explores HRIS adoption through a psychosocial lens, centering the experiences of business line managers, key users who are often excluded from HRIS design, training, and research. Drawing on 25 qualitative interviews across five large UK-based organizations, this paper identifies six emergent themes related to interpersonal trust, role identity, leadership influence, organizational culture, emotional resistance, and the gap between expected usefulness and daily utility. Findings reveal that approaches which account for user emotions, perceived role clarity, and social context offer a more complete understanding of HRIS adoption than those based solely on intention or usability. By highlighting the role of interpersonal dynamics and subjective experience, this study challenges dominant technology adoption models and contributes to more human-centered perspectives in HRIS research and practice. This paper concludes by offering theoretical implications and practical guidance for designing HRIS strategies that reflect the psychosocial realities of implementation across diverse organizational environments.
This article belongs to the Section Cognitive Psychology
Keywords: 35 Commerce, Management, Tourism and Services; 3503 Business Systems In Context; 3507 Strategy, Management and Organisational Behaviour; 46 Information and Computing Sciences; 4609 Information Systems; Behavioral and Social Science; Clinical Research; 3 Good Health and Well Being; Human Resource Information Systems (HRISs); psychosocial factors; managerial engagement; technology adoption; organizational behavior; organizational psychology; digital transformation